2019
DOI: 10.1111/cas.13893
|View full text |Cite
|
Sign up to set email alerts
|

Augmented antitumor activity of 5‐fluorouracil by double knockdown of MDM4 and MDM2 in colon and gastric cancer cells

Abstract: Inactivation of the TP53 tumor suppressor gene is essential during cancer development and progression. Mutations of TP53 are often missense and occur in various human cancers. In some fraction of wild‐type (wt) TP53 tumors, p53 is inactivated by upregulated murine double minute homolog 2 (MDM2) and MDM4. We previously reported that simultaneous knockdown of MDM4 and MDM2 using synthetic DNA‐modified siRNAs revived p53 activity and synergistically inhibited in vitro cell growth in cancer cells with wt TP53 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Among these genes, MDM4 has been reported to play an important role in negative regulation of the tumor suppressor p53 through its interaction with MDM2 (Gansmo et al, 2015[ 7 ]). MDM4/ MDM2 double knockdown with siRNAs enhanced 5-fluorouracil (5-FU)-induced p53 activation, arrested cell cycle at G1 phase, and potentiated the antitumor effect of 5-FU in wtTP53/highMDM4 human colon cancer cells (Imanishi et al, 2019[ 10 ]). Suda et al showed that MDM4 was abnormally expressed in CRC tumor tissues compared with levels in matched normal mucosa and speculated that MDM4 might play a role in colorectal carcinogenesis (Suda et al, 2011[ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, MDM4 has been reported to play an important role in negative regulation of the tumor suppressor p53 through its interaction with MDM2 (Gansmo et al, 2015[ 7 ]). MDM4/ MDM2 double knockdown with siRNAs enhanced 5-fluorouracil (5-FU)-induced p53 activation, arrested cell cycle at G1 phase, and potentiated the antitumor effect of 5-FU in wtTP53/highMDM4 human colon cancer cells (Imanishi et al, 2019[ 10 ]). Suda et al showed that MDM4 was abnormally expressed in CRC tumor tissues compared with levels in matched normal mucosa and speculated that MDM4 might play a role in colorectal carcinogenesis (Suda et al, 2011[ 32 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MDM4 has an elevated expression that correlates with lymph node metastasis [ 164 ]. Inversely, the downregulation of MDM4 increases slightly the activity of cytotoxic drugs (5-FU) in GC cells [ 168 ]. Another example is the LIM domain protein ENIGMA , whose overexpression is caused by SRF [ 165 ].…”
Section: Tp53 a Guardian Against Gastric Cancmentioning
confidence: 99%
“…Immunoblot analysis: Immunoblot analysis was performed as described previously (16). To circumvent the low linear dynamic range of immunoblot analysis, serially diluted total protein extracts from MDM4-NUGC4 cells and undiluted extracts from EGFP-NUGC4 cells were electrophoresed and probed for MDM4 levels.…”
Section: Experiments Using An Mdm4-overexpressing Cell Line Cell Linmentioning
confidence: 99%